Initial collection of an inadequate 24-hour urine sample in children does not predict subsequent inadequate collections. Issue 1 (February 2019) - Chan, K.H.; Moser, E.A.; Whittam, B.M.; Misseri, R.; Cain, M.P.; Krambeck, A.; Schwaderer, A.
Summary: Introduction: Approximately half of adult stone formers submit specimens that are either under or over collections as determined by 24-h creatinine/kg. Previously identified predictors of inadequate collection in adults include female sex, older age, higher body mass index (BMI), vitamin D supplementation, and weekday collection. Objective: The objective of this study is to determine risk factors for inadequate 24-h urinary specimen collection in the pediatric population. Study design: A retrospective analysis of all children (<18 years of age) with renal and/or ureteral calculi evaluated at the study tertiary care pediatric center from 2005 to 2015 was performed. Those who had at least one 24-h urinary metabolic profile after a clinical visit for kidney and/or ureteral stones were included; children with bladder stones were excluded. Adequate collections had a urine creatinine of 10–15 mg/kg/24 h. A bivariate analysis of potential factors associated with inadequate collection of the initial urinary metabolic profile, including child demographics, parental socio-economic factors, history of stone surgery, and weekday vs. weekend urine collection, was performed. A mixed-effects logistic regression, controlling for correlation of specimens from the same patient, was also performed to determine whether an initial inadequate collection predicted a subsequent inadequate collection. Results: Of 367 patients, 80 had an adequate collection (21.9%): median age, 13 years (interquartile range, 8–16); 61.1% female; 93.5% white; 19.5% obese; and 13.0% overweight. No parental or child factors were associated with inadequate collection (Summary Table). Of inadequate collections, more than 80% were over collections. In the 175 patients with more than one 24-h urinary specimen collection, the effect of an initial inadequate collection on subsequent inadequate collections was not significant after controlling for the correlation of samples from the same patient (p = 0.8). Discussion: Any parental or child factors associated with the collection of inadequate 24-h urine specimens in children were not found. An initial inadequate collection does not predict subsequent inadequate collections. It was surprising that >80% of the inadequate collections were over collections rather than under collections. Possible explanations are that children collected urine samples for longer than the 24-h period or that stone-forming children produce more creatinine per 24-h period than healthy children due to hyperfiltration. Conclusion: Inadequate collections are very common, and the risk factors for them are unclear. A repeat collection would be suggested if the first is inadequate. Further studies must be planned to explore barriers to accurate specimen collection using qualitative research methodology.